Influence and Mechanism Research of Hydration Heat Inhibitor on Low-Heat Portland Cement - Jia, Fujie; Yao, Yan; Wang, Jingyu (Frontiers in Materials, 2021)
A kind of microcapsule sustained-release type hydration heat inhibitor (MSR) was prepared. The effect of MSR on semi-adiabatic temperature rise, setting time and strength of low-heat Portland cement was investigated. Microcalorimeter, XRD, SEM and TG-DSC were used to investigate the mechanism of MSR on hydration of low-heat Portland cement. The results showed that MSR had good regulating effect on hydration of low-heat Portland cement. When the dosage of MSR was 0.3%, the heat release rate decreased by 10% and the peak temperature decreased by 52%. The 3-d compressive strength decreased by 50%, and the 28-d strength was the same as control. MSR can delay the hydration of low-heat Portland cement by inhibiting the heat release rate of C2S and C3S minerals.